An Analysis of Teacher Strategies for Improving the Quality of Fiqh Learning - Amin, Rifadlin; Ahmad, Samlan; Soleman, Amanan; Hidayatullah, Achmad Faqi; Rusydianti, Alhimna (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2024)
Education is one of the important factors in the progress of the nation. Quality learning is one of the supporting factors in producing quality students too. This research aims to find out teachers' strategies for creating effective, efficient, and quality learning. This research uses a qualitative method with a case study approach. Data sources were taken from fifteen informants through in-depth and group interviews as well as document analysis. All informants were selected using purpose sampling techniques. The informants in this research were one school principal, one curriculum representative, two fiqh teachers, and ten Madrasah Aliyah students. The results of this research show that the four teacher strategies for improving the quality of fiqh learning are i) apperception, ii) use of varied learning methods, iii) selecting appropriate learning media, iv) evaluation. It is hoped that this research can become evaluation material for educators and can also increase knowledge for readers.